2020
DOI: 10.3390/genes11040385
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of IRF7 Highlights its Modulator Function of Host Response Against Avian Influenza Virus and the Involvement of MAPK and TOR Signaling Pathways in Chicken

Abstract: Interferon regulatory factor 7 (IRF7) is known as the master transcription factor of the type I interferon response in mammalian species along with IRF3. Yet birds only have IRF7, while they are missing IRF3, with a smaller repertoire of immune-related genes, which leads to a distinctive immune response in chickens compared to in mammals. In order to understand the functional role of IRF7 in the regulation of the antiviral response against avian influenza virus in chickens, we generated IRF7-/- chicken embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Kim et al. [ 87 ] showed that a knockout of IRF7 in chicken DF-1 cells, and subsequent AIV infection, resulted in the altered gene expression pattern of several genes, including key immune response genes such as IL12 , FOS , and AP1 . The authors further suggest that this shift in expression pattern could be a compensation for the absence of IRF7 [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al. [ 87 ] showed that a knockout of IRF7 in chicken DF-1 cells, and subsequent AIV infection, resulted in the altered gene expression pattern of several genes, including key immune response genes such as IL12 , FOS , and AP1 . The authors further suggest that this shift in expression pattern could be a compensation for the absence of IRF7 [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…In chicken trachea, FOS was shown to be upregulated after hydrogen-sulfide-induced oxidative stress, revealing the importance of FOS/IL8 signaling during tracheal inflammation [86]. Kim et al [87] showed that a knockout of IRF7 in chicken DF-1 cells, and subsequent AIV infection, resulted in the altered gene expression pattern of several genes, including key immune response genes such as IL12, FOS, and AP1. The authors further suggest that this shift in expression pattern could be a compensation for the absence of IRF7 [87].…”
Section: Master Regulatorsmentioning
confidence: 99%
“…The absence of IRF3 and key role of chIRF7 were confirmed by analyzing de novo assembled RNA-seq data in response to the dsRNA viral mimic poly (I:C), following IRF7 knockdown or overexpression (Kim and Zhou 2015). Ultimately, knockout of IRF7 in the DF-1 chicken embryonic fibroblast cell line (Cheng et al 2019b;Kim et al 2020) greatly decreased expression of type I interferon. In birds, two serologically distinct types of type I interferon genes have been identified on the Z chromosome (Sick et al 1996).…”
Section: Toll-like Receptors and Supramolecular Organizationmentioning
confidence: 89%
“…However, IRF7 can be coimmunoprecipitated with Smad3 [ 43 ], which also interact with TGIF1 [ 19 ]. Furthermore, the deletion of IRF7 hinders the upregulation of genes in the MAPK pathway [ 44 ], which is upstream of TGIF1 phosphorylation [ 45 ]. Therefore, although a link between IRF7 and TGIF1 has been observed and the IRF7-TGIF1 axis has been implicated, the molecular mechanism requires further investigation.…”
Section: Discussionmentioning
confidence: 99%